(untitled) (MAUSAM, 1977)
A non-linear model for the rainfall run-off relation is discussed by using the Laplace’s transform in the equation of continuity and storage. The equation of continuity has been converted into a nth order algebraic equation. A simple integration method has also been indicated for the constant input function. Some particular cases are also discussed as a verification of the result, and lastly the linear modern has been deduced as a special case from the non-linear model. The results are in close agreement with that of observed hydrograph.